TAXPAYER PURCHASE DECISIONS ANALYSIS OF ELECTRONIC SERVICES OFFERED BY PAJAKKU.COM AS PARTNER OF THE DIRECTORATE GENERAL OF TAXES - Fung, Ng In; Murni, Yanti (SWOT : Jurnal Ilmiah Ilmu Manajemen, 2022)
This study aimed to determine the effect of price, promotion and ease of use of the product or service application to purchase decisions. In this study the survey method was used. The population is 100 taxpayers who have used the product or service application of PT Mitra Pajakku (Pajakku.com). Sampling using purposive sampling using a questionnaire. The method used is multiple regression analysis. The results show that price, promotion and ease of use of the product or service application partially have a positive and significant effect on purchasing decisions. Evidence from the results of multiple linear analysis test which shows the significant value of the variables that support the hypothesis. Therefore, the results of this study state that there is an influence on the price, promotion, ease of use of the product or service of Pajakku.com application to the purchase decision made by Taxpayers of Pajakku.com